Indonesian Muslim Feminism's Criticism of the Practice of Cutting Female Genitalia from a Human Rights Perspective - Anizar Ayu Pratiwi (Journal of Islamic Mubadalah, 2024)
This article analyzes the Indonesian feminist critique represented by the Indonesian Women Ulema group, this critique is related to the discrimination of women in the context of female circumcision. The purpose of this article is to analyze the reasons why Indonesian Muslim feminist critics attack female circumcision, and how female circumcision is viewed from a human rights perspective. This article uses a qualitative method, the type of article library research / literature study that examines the reasons for Indonesian Muslim feminists who prohibit circumcision for women, data collection techniques through extracting literature related to the prohibition of female circumcision, the theory used is the theory of human rights. The results show that the criticism of Indonesian Muslim feminists who prohibit circumcision for women is that female circumcision causes kemadhorotan (damage), circumcision for women is contrary to women's human rights, this refers to the International Convention on women. The contribution of this article is shown for the legislative government to make a policy to prohibit the act of P2GP / female circumcision.